2008
DOI: 10.1111/j.1365-2664.2008.01488.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and deepening of the North Sea fish assemblage: a biotic indicator of warming seas

Abstract: Summary 1.Climate change impacts have been observed on individual species and species subsets; however, it remains to be seen whether there are systematic, coherent assemblage-wide responses to climate change that could be used as a representative indicator of changing biological state. 2. European shelf seas are warming faster than the adjacent land masses and faster than the global average. We explore the year-by-year distributional response of North Sea bottom-dwelling (demersal) fishes to temperature chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
472
4
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 653 publications
(502 citation statements)
references
References 41 publications
17
472
4
9
Order By: Relevance
“…Prior to 2003 this fish Impacts of the Oceans on Climate Change 37 Author's personal copy was confined to the south and west of the British Isles, but it now extends as far north as the Barents Sea and Spitzbergen (Kirby et al, 2006;Harris et al, 2007). The pelagic environment is of course three-dimensional and recent research has observed a movement of fish species towards deeper cooler waters in response to climate warming (Dulvy et al, 2008). This change can be seen as analogous to the upward altitudinal movement of terrestrial organisms in alpine environments.…”
Section: Migration Of Plankton Fish and Benthos Towards The Polesmentioning
confidence: 99%
“…Prior to 2003 this fish Impacts of the Oceans on Climate Change 37 Author's personal copy was confined to the south and west of the British Isles, but it now extends as far north as the Barents Sea and Spitzbergen (Kirby et al, 2006;Harris et al, 2007). The pelagic environment is of course three-dimensional and recent research has observed a movement of fish species towards deeper cooler waters in response to climate warming (Dulvy et al, 2008). This change can be seen as analogous to the upward altitudinal movement of terrestrial organisms in alpine environments.…”
Section: Migration Of Plankton Fish and Benthos Towards The Polesmentioning
confidence: 99%
“…On average, the assemblage has deepened by 3.6 m decade 21 , belying exceptional changes in species such as cod Gadus morhua (figure 4c) and anglerfish Lophius piscatorius (figure 4a; Dulvy et al 2008). A widespread change in depth is a predictably efficient response for species as tracking the movement of their thermal optima requires smaller movements with depth or elevation than for latitude (Colwell et al 2008).…”
Section: Temperate Fisheries: the North Seamentioning
confidence: 99%
“…Because the northward emigration of larger, cold-water species progressed more gradually (Perry et al 2005), diversity increased within the North Sea ( figure 4e,f ). Southward movements of warm-water species such as sole Solea solea and scaldfish Arnoglossus laterna into the shallow southern North Sea have also occurred owing to earlier springtime warming (Dulvy et al 2008).…”
Section: Temperate Fisheries: the North Seamentioning
confidence: 99%
See 1 more Smart Citation
“…Major biogeographical shifts have been observed in recent years (Perry et al 2005;Dulvy et al 2008) but the cause and effect of such change remains poorly understood. For example, a poleward shift in North Sea fishes appears to occur at subcritical temperatures (Perry et al 2005), but it is still not known whether biogeographical shifts occur as a result of behavioural redistributions (behavioural thermoregulation), localised extinctions or community-level interactions.…”
Section: Reproductive Behaviourmentioning
confidence: 99%